2016
DOI: 10.1002/ange.201604662
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between Criegee Intermediates and the Inorganic Acids HCl and HNO3: Kinetics and Atmospheric Implications

Abstract: Criegee intermediates (CIs) are a class of reactive radicals that are thought to play a key role in atmospheric chemistry through reactions with trace species that can lead to aerosol particle formation. Recent work has suggested that water vapor is likely to be the dominant sink for some CIs, although reactions with trace species that are sufficiently rapid can be locally competitive. Herein, we use broadband transient absorption spectroscopy to measure rate constants for the reactions of the simplest CI, CH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
(71 reference statements)
1
27
2
Order By: Relevance
“…TS1 obtained here differs from the transition state between the pre-reactive complex and CMHP found in Ref. 16, where it lies lower in energy than the HCl-CH 2 OO complex. This fact may be attributedt ot he small basis set employed in their calculations, cc-pVDZ.…”
contrasting
confidence: 84%
“…TS1 obtained here differs from the transition state between the pre-reactive complex and CMHP found in Ref. 16, where it lies lower in energy than the HCl-CH 2 OO complex. This fact may be attributedt ot he small basis set employed in their calculations, cc-pVDZ.…”
contrasting
confidence: 84%
“…Reaction rates of Criegee intermediates with HNO 3 and HCl have been shown to approach or exceed the gas kinetic limit. 49,50 Both reaction types are predicted to form hydroperoxide adduct products, similar to the reactions with carboxylic acids. The hydroperoxide adducts from reaction with hydrochloric and nitric acids also have chloro and nitrate functionalities, respectively, both of which are important in atmospheric chemistry.…”
Section: Acs Earth and Space Chemistrymentioning
confidence: 86%
“…Laboratory experiments and theoretical calculations have shown SCIs to oxidise SO 2 (e.g. Cox and Penkett, 1971;Welz et al, 2012;Taatjes et al, 2013), organic (Welz et al, 2014) and inorganic (Foreman et al, 2016) acids (Vereecken, 2017) and a number of other important trace gases found in the atmosphere, as well as forming adducts with NO 2 (Taatjes et al, 2014;Vereecken and Nguyen, 2017;Caravan et al, 2017). Measurements in a boreal forest (Mauldin III et al, 2012) and at a coastal site (Berresheim et al, 2014) have both identified a missing process (in addition to a reaction with OH) that oxidises SO 2 to H 2 SO 4 , potentially arising from SCI reactions.…”
Section: Introductionmentioning
confidence: 99%